Напрями соціального захисту державних службовців в Україні - Безусий, В. В.; Bezusyi, V. V.; ORCID: http://orcid.org/0000-0001-6452-5672 (Науковий вісник публічного та приватного права. - 2019. - Вип. 4, т. 1. - С. 172-179, 2019)
Проаналізовано напрями соціального захисту державних службовців в Україні. Деталізовано зміст законодавства у вказаній царині. Виведено авторський перелік напрямів соціального захисту державних службовців в Україні:1) матеріальний напрям; 2) соціально-побутовий напрям; 3) оздоровчо-рекреаційний напрям; 4) пенсійний напрям. Охарактеризовано роль і сутність кожного з них.

In the article the directions of social protection of civil servants in Ukraine are analyzed. The content of the legislation in that area is detailed. The scientific approaches to the research question are presented. The author lists the directions of social protection of civil servants in Ukraine. The role and nature of each of them are described. It is found that the following types of bonuses can be set for civil servants: 1) a bonus based on the annual performance appraisal; 2) monthly or quarterly premium in accordance with a personal contribution to the overall result of the work of a state body. The criteria for awarding the award include: 1) initiative in work; 2) the quality of the performance of the tasks defined by the regulations on the state body, the independent structural unit in which the civil servant works, his job description, as well as the instructions of the management of the relevant state body and the direct head of the civil servant; 3) the urgency of the tasks; 4) performing additional tasks. It is determined that a bonus for the rank of a civil servant is an overpayment to a fixed-term salary of a civil servant, determined by the Cabinet of Ministers of Ukraine Resolution on the Remuneration of Employees of State Bodies, which is paid for his special title, which reflects the official status of the official given the position he occupies, his professional competence, training and length of service for which civil servants. It is concluded that the material direction of social protection of civil servants is characterized by the following features: it is implemented in the form of allowances, surcharges, bonuses and compensations; the size of such types of social protection is either directly provided for by law or directly determined by the head of the civil service; the types of material direction of social protection of civil servants are, in essence, part of his salary, and are introduced with the aim of providing additional social protection to civil servants, in view of the functions they perform and the risks they face.

Проанализированы направления социальной защиты государственных служащих в Украине. Детализировано содержание законодательства в указанной области. Выведен авторский перечень направлений социальной защиты государственных служащих в Украине: 1) материальное направление; 2) социально-бытовое направление; 3) оздоровительно-рекреационное направление; 4) пенсионное направление. Охарактеризованы роль и сущность каждого из них.
Безусий, В. В. Напрями соціального захисту державних службовців в Україні / Безусий В. В // Науковий вісник публічного та приватного права. - 2019. - Вип. 4, т. 1. - С. 172-179. - DOI: https://doi.org/10.32844/2618-1258.2019.4-1.29.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; державні службовці; government officials; государственные служащие; соціальний захист; social protection; социальная защита; соціальне забезпечення; social welfare; социальное обеспечение; державна служба; public service; государственная служба